Comparative Analysis of Lactobacillus plantarum WCFS1 Transcriptomes by Using DNA Microarray and Next-Generation Sequencing Technologies - Leimena, Milkha M. (American Society for Microbiology, 2012)
RNA sequencing is starting to compete with the use of DNA microarrays for transcription analysis in eukaryotes as well as in prokaryotes. The application of RNA sequencing in prokaryotes requires additional steps in the RNA preparation procedure to increase the relative abundance of mRNA and cannot employ the poly(T)-primed approach in cDNA synthesis. In this study, we aimed to validate the use of RNA sequencing (direct cDNA sequencing and 3′-untranslated region [UTR] sequencing) using Lactobacillus plantarum WCFS1 as a model organism, employing its established microarray platform as a reference. A limited effect of mRNA enrichment on genome-wide transcript quantification was observed, and comparative transcriptome analyses were performed for L. plantarum WCFS1 grown in two different laboratory media. Microarray analyses and both RNA sequencing methods resulted in similar depths of analysis and generated similar fold-change ratios of differentially expressed genes. The highest overall correlation was found between microarray and direct cDNA sequencing-derived transcriptomes, while the 3′-UTR sequencing-derived transcriptome appeared to deviate the most. Overall, a high similarity between patterns of transcript abundance and fold-change levels of differentially expressed genes was detected by all three methods, indicating that the biological conclusions drawn from the transcriptome data were consistent among the three technologies.